2015
DOI: 10.1021/acsami.5b09291
|View full text |Cite
|
Sign up to set email alerts
|

p-Type NiO Hybrid Visible Photodetector

Abstract: A novel hybrid visible-light photodetector was created using a planar p-type inorganic NiO layer in a junction with an organic electron acceptor layer. The effect of different oxygen pressures on formation of the NiO layer by pulsed laser deposition shows that higher pressure increases the charge carrier density of the film and lowers the dark current in the device. The addition of a monolayer of small molecules containing conjugated π systems and carboxyl groups at the device interface was also investigated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 20 publications
0
21
2
Order By: Relevance
“…The changes in the acceptor concentrations for three samples are consistent with their photocurrent values, that is, the larger N A , the better photocurrent performance will be. While our result is different from the one reported by Mallows et al, 22 who showed that the higher oxygen pressure effectively increased the amount of nickel vacancies, leading to 1 order enhancement in acceptor concentrations.…”
Section: Results and Discussioncontrasting
confidence: 99%
“…The changes in the acceptor concentrations for three samples are consistent with their photocurrent values, that is, the larger N A , the better photocurrent performance will be. While our result is different from the one reported by Mallows et al, 22 who showed that the higher oxygen pressure effectively increased the amount of nickel vacancies, leading to 1 order enhancement in acceptor concentrations.…”
Section: Results and Discussioncontrasting
confidence: 99%
“…The hybrid PDs based on p‐type organic molecules with tunable functionality and n‐type inorganic semiconductors with superior intrinsic carrier mobility, usually present high photodetecting performance, thanks to the efficient separation and transfer of photoinduced charge carriers resulting from the p‐n heterojunctions. Various kinds of organic materials, such as polyaniline (PANI),90 poly(vinyl alcohol) (PVA),91 poly(arcylonitrile) (PAN),27 poly(vinyl carbazole) (PVK),92 polypyrrole (PPy),93 and even pyrene‐tricyanofuran derivatives,94,95 are also adopted to modify the photoelectric properties of semiconductor‐based PDs 96…”
Section: Materials For Heterojunction Uv Pdsmentioning
confidence: 99%
“…So far, PDs based on single crystal, film, and nanostructured materials have been applied for building designed PDs to detect ultraviolet [12][13][14], visible [15][16][17][18], or infrared [19][20][21][22][23][24][25] photons with actual needs. For example, highly narrow band (bandwidth of 10 nm) solar-blind photodetectors of β-Ga 2 O 3 single crystals with a peak responsivity of 0.23 A/W at 262 nm and an EQE of 110% were reported [26].…”
Section: Introductionmentioning
confidence: 99%